Sejarah kebudayaan Bali kajian perkembangan dan dampak pariwisata penulis, Supratikno Raharjo, Agus Aris Munandar, Susanto Zuhdi - RAHARJO, Supratikno; Munandar, Agus Aris; Zuhdi, Susanto (1998)
xx, 214 hlm ilus 21 cm